2013
DOI: 10.1175/jcli-d-12-00158.1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Diurnal Cycle of Rainfall Associated with the MJO Observed by a Dense Hourly Rain Gauge Network at Sarawak, Borneo

Abstract: This study investigates spatiotemporal characteristics of the diurnal cycle (DC) of rainfall over Sarawak in northwest Borneo Island, associated with large-scale intraseasonal disturbances represented by the Madden-Julian oscillation (MJO). This is accomplished using a dense hourly rain gauge network and satellite data. The spatial pattern of the DC is classified into two major groups, coastal and interior regions, based on remarkable differences in rainfall peak times and amplitudes. Amplitudes of the DC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 41 publications
7
45
0
2
Order By: Relevance
“…At any time, rainfall values from no more than 8% of total rain gauges are missing, and in total such events accounts for less than 1.5% of total study period. The detailed information on these rain gauges and their data quality check procedure are provided in Kanamori et al [] and also in Wong et al [] and Tan et al []. In addition, the Asian Precipitation‐Highly‐Resolved Observational Data Integration Toward Evaluation (APHRODITE) gridded rainfall data set, which is available at 0.25° × 0.25° spatial resolution over monsoonal Asia [ Yatagai et al ., ], is also evaluated to examine its suitability over the MC region as Tan et al [] comparisons of the APHRODITE product with ground observations over Sarawak were limited to few points to pixels only.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At any time, rainfall values from no more than 8% of total rain gauges are missing, and in total such events accounts for less than 1.5% of total study period. The detailed information on these rain gauges and their data quality check procedure are provided in Kanamori et al [] and also in Wong et al [] and Tan et al []. In addition, the Asian Precipitation‐Highly‐Resolved Observational Data Integration Toward Evaluation (APHRODITE) gridded rainfall data set, which is available at 0.25° × 0.25° spatial resolution over monsoonal Asia [ Yatagai et al ., ], is also evaluated to examine its suitability over the MC region as Tan et al [] comparisons of the APHRODITE product with ground observations over Sarawak were limited to few points to pixels only.…”
Section: Methodsmentioning
confidence: 99%
“…On subdaily scale comparison, they found that all the five products exhibit a similar diurnal rainfall maximum in late afternoon but with varying amplitude differences. However, over the Sarawak region of Malaysia, Kanamori et al [] found no significant difference in the amplitude of diurnal cycle of rainfall between the observation and the TRMM 3B42V6 products, albeit with a delayed peak time of maximum rainfall in 3B42V6. In addition, they found that TRMM 3B42V6 generally tends to underestimate rainfall over interior areas of Sarawak, whereas it overestimates rainfall along the coast.…”
Section: Introductionmentioning
confidence: 99%
“…Important relationships between the MJO and precipitation variability have also been found over South America (e.g., Nogués-Paegle et al, 2000;Carvalho et al, 2002;Carvalho et al, 2004;Liebmann et al, 2004;Souza and Ambrizzi, 2006;Muza et al, 2009), Africa (Pohl and Camberlin, 2006), Mexico (Mo and Higgins, 1998a), United States (e.g., Mo and Higgins, 1998b;Jones, 2000;Jones and Carvalho, 2012;Zhou et al, 2012), Canada (Lin et al, 2010), Australia (Wheeler et al, 2009), Indonesia (e.g. Kanamori et al, 2013;Peatman et al, 2014), and China (e.g., Zhang et al, 2009;Jia et al, 2011). The MJO also affects monsoon systems (e.g., Hartmann and Michelsen, 1989;Hendon and Liebmann, 1990;Jones and Carvalho, 2002;Matthews, 2004;Pai et al, 2009).…”
Section: Problem Descriptionmentioning
confidence: 95%
“…Around midnight, the rainfall moves from the land to the surrounding water, reaching a peak in the early morning before dissipating around noon. This phenomenon has been frequently documented for the Maritime Continent region, via surface observations (Houze et al, ; Johnson & Priegnitz, ; Kamimera et al, ; Kanamori et al, ), satellite observations (Ichikawa & Yasunari, ; Keenan & Carbone, ; Kikuchi & Wang, ; Nesbitt & Zipser, ; Williams & Houze, ; Yamamoto et al, ; Yang & Slingo, ), and numerical simulations (Love et al, ; Sato et al, ).…”
Section: Introductionmentioning
confidence: 84%